DEVELOPMENT OF A STAND ALONE MONITORING SYSTEM (S.A.MO.S.) - Kosmatopoulos, C.; Tsagourias, N. (International Journal of Computing, 2002)
Environmental monitoring is nowadays a common instrumentation application, not only in cases where scientific information is needed, but also for pollution control and development planning of certain sensitive areas. This paper describes the development of a Stand Alone Monitoring System (S.A.MO.S.) which is actually a complete monitoring station for environmental measurements in rivers, lakes, lagoons and other sensitive ecosystems. S.A.MO.S. is capable of performing scheduled measurements by sensors or other independent electronic measuring instruments, and stores data locally in a memory module. Measurement data may then be transferred to a PC computing system for further analysis either by using cellular phone network or via a UHF transceiver. Validation of measurements is achieved by system’s self check control and warning signals can be sent to authorized personnel in case of errors. The basic features and the configuration of this system are presented in this work.